The Correlation Between Serum Vitamin D Levels with Sleep Quality and Fatigue in Neurology and Psychiatry Trainees Doctors - Putri Rossyana Dewi; Desak Ketut Indrasari Utami; Ida Bagus Kusuma Putra; Anak Agung Ayu Meidiary; I Komang Arimbawa; I Putu Eka Widyadharma (Warmadewa University, 2025)
Health workers, including resident physicians, are integral to delivering healthcare services. Engagement in both physical and non-physical tasks under rotating shift schedules may adversely impact sleep quality and precipitate fatigue among this cohort. Given the existing evidence, this study aims to examine the correlation between serum vitamin D levels, sleep quality, and fatigue among resident doctors. An analytical cross-sectional study was performed at Ngoerah Hospital from May to June 2022. Serum 25-hydroxy vitamin D [25(OH)D] concentrations were quantified to ascertain vitamin D status. Sleep quality was evaluated using the Pittsburgh Sleep Quality Index (PSQI), and fatigue severity was measured via the Fatigue Severity Scale (FSS). Serum 25(OH) D levels demonstrated a strong and statistically significant negative correlation with PSQI scores (r = -0.664, p<0.001) and with FSS scores (r = -0.734, p<0.001). Regression analysis revealed that each one-unit increase in serum vitamin D was associated with a 65.7% reduction in PSQI score and a 68.2% reduction in FSS score. Most participants exhibited insufficient to deficient vitamin D status, likely attributable to limited occupational sun exposure. Monitoring and management of vitamin D status, including education on adequate sunlight exposure and consideration of vitamin D supplementation, are critically important for healthcare professionals, who are at elevated risk for deficiency, to support optimal sleep quality and minimize fatigue that may adversely affect clinical performance.